ANALISIS PERANCANGAN SISTEM MATV (MASTER ANTENA TELEVISI) DIGITAL PADA HOTEL GOLDEN TULIP ESSENTIAL PONTIANAK - ., Ary Hidayat (Jurnal Teknik Elektro Universitas Tanjungpura, 2015)
ABSTRAC Developments in information technology and multimedia communication at this moment is growing rapidly. One of them is the development of multimedia where MATV used as an information media and entertainment at ​​hotels and apartments. the historical development of television is a technology CATV / Cable TV are known before the advent of new technologies MATV. MATV consists of two types of technology that is digital and analog. MATV is based on two types of differences, although not significant, the difference was only found in the main device is the modulator. If the Digital MATV one modulator unit can operate 4 unit receiver then it can not be done by MATV Analog. Because MATV Analog can only run one unit of Modulator. the results of research conducted by the TV standard parameter with a range of 60 dB to 80 dB. object of research taking samples at Hotel Golden Tulip Essential Pontianak with the output of view that is quite good. the value achieved is still in the measurement standard that is 68 dB, this shows that the system used to work optimally with good quality TV viewing. MATV Digital is a high-resolution TV with High Definition Television (HDTV) is a digital television standard internationa which is broadcast in 16: 9 format television while analog 4: 3. Digital MATV can accommodate broadcast in 1 package due to the use of bandwidth in Digital MATV with greater resolution. The reliability of the MATV Digital that uses the S-Band frequency makes the displayed image remains in good condition without being affected by the weather disturbance. Digital MATV not have an influence on the distance of the transmitting station. It happens because Digital TV receive signals directly from the satellite frequency or Digital broadcasting. when the system is running it creates a new channel from 1 st floor to the 11 th floor and still run according to procedure although the location of the transmitter far from the station transmitter, the results remain good image display without the overlap in different broadcast signals. Key words: Digital MATV, CATV